An evaluation of food label reading habits of individuals working in hospitals - Çakırer Çalbayram, Nazan; Yardımcı, Hülya; Aydın, Bahise (Progress in Nutrition, 2018)
Aim: The aim of this study is to determine food label reading habits of individuals working in hospitals, and raise awareness about food label reading with the help of a data collection form prepared based on the topic.  Material/Methods: The research was carried out with 336 people (76 males, 260 females) between the ages of 19-60 working in various hospitals in Ankara city.  Results: In this work, we found that the mean age of participant was 32.85±8.34 years old and BMI was 23.37±4.02 kg/m². 53.9% of the individuals stated that the most influential factor to purchase a packaged food product was their own preference. It was determined that 44.6% of the individuals always read the label of a packaged food product. 36.9% stated that this information was always effective in purchasing, and 57.1% reported the information was occasionally influential. Conclusion: Food labels can help promote the awareness of consumers about nutrition, and access right information.